Molecular detection of Coxiella burnetii in horse sera in Iran - Khademi, P (Comp Immunol Microbiol Infect Dis, 2020)
Coxiella burnetii is a zoonotic bacterium that can infect a wide range of animals including horses. However, its circulation dynamics in and through horses are still unclear. The aim of this study was to evaluate prevalence of C. burnetii and its genomic characteristics in horse sera samples in the North of Iran (Golestan Province). The samples were collected in 2018 and the age, sex, and breed of each animal were recorded. Nested-PCR was used to detect C. burnetii based on the presence of the transposable gene IS1111. The results showed that 7.50 % (P < 0.05; 95 % CI: 0.5 %–0.12 %) of the examined sera samples were positive for C. burnetii. Based on the resuls, prevalence of C. burnetii in the age groupof < Years 1–5 (p-value <0.05, 95 % CI: 1 %–8 %) was less than the age group of >6 years old (p-value <0.05, 95 %, CI: 7 %–19.8 %). In previous studies, it was concluded that the horses' population in Golestan Province should be considered as an important factor in the epidemiology of Q fever and consequently in public health. Further studies should be implemented to evaluate if horses may be relevant indicators of zoonotic risk in urban and suburban endemic areas.